2021
DOI: 10.33806/ijaes2000.21.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Autonomous Language Learning at Tertiary Education Level in Saudi Arabia: Students’ and Instructors’ Perceptions and Practices

Abstract: The ultimate goal of educational institutions is to create self-independent, lifelong learners and discourage regurgitation of information in exams and evaluation. Thus, this study investigated (a) autonomous learning perceptions and practices among Saudi EFL students (n=312) and (b) instructors’ perceptions of their student’s autonomous language learning at a rural college at Jouf University in Saudi Arabia. This study utilizes a mixed method explanatory sequential research design using both quantitative (que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
1
1
0
2
Order By: Relevance
“…The finding of this study also corroborates the result of Mawlawi Diab (2015) who concluded that the method of giving feedback plays an important role in language development. Moreover, this finding aligns with that of Khreisat and Mugableh (2021) whose participants attributed 25% of L2 writing effectiveness to activities requiring collaboration between teachers and students, which highlights the importance students allot to participation in their own learning.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The finding of this study also corroborates the result of Mawlawi Diab (2015) who concluded that the method of giving feedback plays an important role in language development. Moreover, this finding aligns with that of Khreisat and Mugableh (2021) whose participants attributed 25% of L2 writing effectiveness to activities requiring collaboration between teachers and students, which highlights the importance students allot to participation in their own learning.…”
Section: Discussionsupporting
confidence: 81%
“…Moreover, direct feedback influenced grammatical accuracy while indirect feedback reduced non-grammatical errors (Van Beuningen et al 2012). A recent study (Khreisat and Mugableh 2021) reported that students attributed 50% of the effectiveness of L2 writing classrooms to teachers' feedback, 25% to activities requiring collaboration between teachers and students and another 25 % to student autonomy. Moreover, Ganapathy, Tan and Phan (2020) concluded that TCF significantly improved students' L2 writing skills.…”
Section: Effect Of Corrective Feedback On L2 Writingmentioning
confidence: 99%
“…(13,16,46) Al realizar el análisis de los resultados de la responsabilidad frente a una situación en la educación superior, se evidenció que los estudiantes, docentes e instituciones educativas deben centrarse en 3 factores básicos para desarrollar la autonomía de sus estudiantes, estos son: capacidad, voluntad y la oportunidad; en tal sentido tanto los estudiantes y los docentes deben llevar cursos de autonomía con la finalidad de formar estudiantes autónomos; de lo anterior se desprende que la autonomía de los estudiantes implica una relación comprometida docente-alumno; es así como la responsabilidad del aprendizaje es un evento compartido; se desprende que los estudiantes que asumen responsabilidades compartidas con el docente, no tienen mucha confianza en sí mismo; y los docentes deben evaluar el aprendizaje de los estudiantes. (11,13,19,27,55) En ese mismo contexto, la práctica activa del estudiante permite su autonomía en su aprendizaje y debe ser monitoreado por el docente; además los cuestionarios en línea permiten al docente retroalimentarlos; en tal sentido el aprendizaje autónomo de los estudiantes se puede mejorar con el desarrollo de los cuestionarios en línea; en la autoevaluación de los estudiantes, el docente juega un rol importante; también los docentes a la hora de planificar sus guías de sus asignaturas deben tener en cuenta las actividades presenciales y no presenciales; también crear guías de aprendizajes para el desarrollo de competencias digítales las cuales los estudiantes deben resuélvelos con herramientas digitales, así desarrollando su aprendizaje autónomo. (12,15,16,17,54) Por otro lado, los estudiantes deben desarrollarse en el trabajo colaborativo; primero hacer un trabajo individual responsable luego hacer el trabajo en grupo; el docente debe usar metodologías activas para el desarrollo del autoaprendizaje, lo que mejora las competencias metodológicas de los estudiantes; también https://doi.org/10.56294/saludcyt2023391 13 Caballero-Cantu JJ, et al la participación activa de los estudiantes en su autoaprendizaje por medio del recurso virtual Postcast, desarrollando el trabajo colaborativo; se debe fomentar el autoaprendizaje de los estudiantes a través de metodología didácticas tales como trabajo en grupo autónomo, individual autónomo combinando con el aula invertida, y aportar documentación digital de ejercicios desarrolladas en clase y extras para que el alumno pueda profundizar su autoaprendizaje.…”
Section: Autoconceptounclassified
“…(18,20,23) De otro lado, los estudiantes piensan que su aprendizaje depende de sus profesores ya sea dentro o fuera del aula; es decir que los alumnos no se consideran completamente autónomos ni independientes del docente, que siempre va existir una dependencia; también perciben que el desarrollo de su aprendizaje está pautado por la relación profesor-alumno en la que cada uno asume un rol equitativo en las aulas. (25,26,27) Salud, Ciencia y Tecnología. 2023; 3:391 14…”
Section: Autoconceptounclassified